A randomized controlled trial of increased dose and frequency of albendazole with standard dose DEC for treatment of Wuchereria bancrofti microfilaremics in Odisha, India. - Shantanu Kumar Kar; Bhagirathi Dwibedi; Anna Salomi Kerketa; Antaryami Maharana; Sudanshu S Panda; Prafulla Chandra Mohanty; John Horton; Cherubala P Ramachandran (Public Library of Science (PLoS), 2015)
Although current programmes to eliminate lymphatic filariasis have made significant progress it may be necessary to use different approaches to achieve the global goal, especially where compliance has been poor and 'hot spots' of continued infection exist. In the absence of alternative drugs, the use of higher or more frequent dosing with the existing drugs needs to be explored. We examined the effect of higher and/or more frequent dosing with albendazole with a fixed 300 mg dose of diethylcarbamazine in a Wuchereria bancrofti endemic area in Odisha, India. Following screening, 104 consenting adults were randomly assigned to treatment with the standard regimen annually for 24 months (S1), or annually with increased dose (800 mg albendazole)(H1) or with increased frequency (6 monthly) with either standard (S2) or increased (H2) dose. Pre-treatment microfilaria counts (GM) ranged from 348 to 459 mf/ml. Subjects were followed using microfilaria counts, OG4C3 antigen levels and ultrasound scanning for adult worm nests. Microfilarial counts tended to decrease more rapidly with higher or more frequent dosing at all time points. At 12 months, Mf clearance was marginally greater with the high dose regimens, while by 24 months, there was a trend to higher Mf clearance in the arm with increased frequency and 800 mg of albendazole (76.9%) compared to other arms, (S1:64%, S2:69.2% & H1:73.1%). Although higher and/or more frequent dosing showed a trend towards a greater decline in antigenemia and clearance of "nests", all regimens demonstrated the potential macrofilaricidal effect of the combination. The higher doses of albendazole did not result in a greater number or more severe side effects. The alternative regimens could be useful in the later stages of existing elimination programmes or achieving elimination more rapidly in areas where programmes have yet to start.